Implementation of Prevention and Investigation Programs in Organizational Oversight - Daud Daud; Ari Gusnita (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to analyze and describe the implementation of the Prevention and Investigation program within the scope of supervisory duties carried out by the Metro City Inspectorate in Indonesia. Research Methodology: A qualitative descriptive method was used to describe the conditions in the Prevention and Investigation Sector. The research sample from the Prevention and Investigation Sector consisted of six individuals: (1) Assistant Inspector for Prevention and Investigation, (2) Intermediate Auditor, (3) Intermediate Pengawas Penyelenggaraan Urusan Pemerintahan Daerah (PPUPD) Officer, (4) Junior Auditor, (5) Laporan Hasil Kekayaan Pejabat Negeri (LHKPN) Administrator, and (6) Head of the Planning, Evaluation, and Reporting Subdivision. The data used were primary and secondary, and the data collection techniques included interviews, collection of related documents, and direct observation. Results: The Prevention and Investigation Program at the Metro City Inspectorate achieved quality supervisory results by implementing a reporting system using the e-LHKPN application, with a significant increase in the e-LHKPN score from 42.37% to 100%. Conclusions: The ongoing program may require mandatory changes to achieve good governance. Limitations: The organizational scope of The Metro City Inspectorate is limited to prevention and investigation programs. Contributions: Improving the quality of the Metro City Inspectorate's organizational oversight function through the implementation of the e-LHKPN.